Prediction of Maternal and Fetal Pharmacokinetics of Dolutegravir and Raltegravir Using Physiologically Based Pharmacokinetic Modeling - Xiaomei I. Liu (2020)
© 2020, Springer Nature Switzerland AG. Background: Predicting drug pharmacokinetics in pregnant women including placental drug transfer remains challenging. This study aimed to develop and evaluate maternal–fetal physiologically based pharmacokinetic models for two antiretroviral drugs, dolutegravir and raltegravir.